2018
DOI: 10.1159/000495097
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-200a Affects the Proliferation of Airway Smooth Muscle Cells and Airway Remodeling by Targeting FOXC1 via the PI3K/AKT Signaling Pathway in Ovalbumin-Induced Asthmatic Mice

Abstract: Background/Aims: The etiology of asthma, which is a complicated disorder with various symptoms, including wheezing, coughing, and airflow obstruction, remains poorly understood. In addition, the effects of microRNAs (miRs) have not been explored. This study explored the effect of microRNA-200a (miR-200a) on airway smooth muscle cells (ASMCs) and airway remodeling in asthmatic mice. Furthermore, we speculated that miR-200a achieves its effect by targeting FOXC1 via the PI3K/AKT signaling pathway based on differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Accordingly, the inhibition of the PI3K/AKT signaling pathway reduced lung inflammation by decreasing the expression of IL-4, IL-6, IL-8, TNF-α, and IgE. 117 Overall, miRNAs can have therapeutic applications in preventing airway inflammation by modulating FOXC1 and other signaling molecules, such as PI3K, AKT, NF-κB, cyclin D1, and TGF-β1.…”
Section: Foxc1-mir Signaling Pathwaymentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, the inhibition of the PI3K/AKT signaling pathway reduced lung inflammation by decreasing the expression of IL-4, IL-6, IL-8, TNF-α, and IgE. 117 Overall, miRNAs can have therapeutic applications in preventing airway inflammation by modulating FOXC1 and other signaling molecules, such as PI3K, AKT, NF-κB, cyclin D1, and TGF-β1.…”
Section: Foxc1-mir Signaling Pathwaymentioning
confidence: 98%
“…miR-200a also inhibits lung tissue fibrosis by suppressing TGF-β1-mediated endothelial-mesenchymal transition via reducing FOXC1 expression. 114117 FOXC1 activates the PI3K/AKT signaling pathway, leading to the phosphorylation and activation of several downstream proteins, such as NF-κB and GSK3-β. 118,119 Cyclin D1 is an important regulator of the cell cycle activated by PI3K/AKT signaling through inhibiting p16INK4a, the cyclin D1 suppressor.…”
Section: Foxc1-mir Signaling Pathwaymentioning
confidence: 99%
“…In biological events, synergism and antagonism effect are main forms of different genes in bringing into play biological function. Numerous studies have documented that the network among miRNA molecules and their target genes is complex and critical for the development of various diseases, in which miRNA usually controlled the expression of their targets [60,61]. However, whether there is synergy effect between miRNAs and target genes still remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/AKT pathway is important for cell growth, differentiation, metabolism, survival, and apoptosis. Numerous studies have demonstrated that the PI3K/AKT pathway participates in the regulation of miRNAs, thereby affecting the proliferation of ASMCs ( Liu Y et al, 2018 ; Wang et al, 2018 ). The PI3K/AKT pathway is involved in promoting ECM expression.…”
Section: Discussionmentioning
confidence: 99%